Iterative student-based testing of automated information-handling exercises - C. K. Ramaiah; Mubarak Sulaiman; A. J. Meadows (Association for Learning Technology, 1995)
Much laboratory teaching of information-handling involves students in evaluating information provided either online or via a computer package. A lecturer can help students carry out these tasks in a variety of ways. In particular, it is customary to provide students with hand-outs, and there is good evidence that such hand-outs are a valuable resource, especially for lower-ability students (see, for example Saloman, 1979). In many of these exercises, students are passive receivers of information, in the sense that they assess the information but do not change it. However, it is sometimes possible to use student feedback to change the original input. In this case, the users' mental models of the system can be employed to modify the user-interface set up by the original designer (see Moran, 1981). A number of experiments have been carried out in the Department of Information and Library Studies at Loughborough University to examine how computer interfaces and instruction sheets used in teaching can be improved by student feedback. The present paper discusses examples of this work to help suggest both the factors to be taken into account and the sorts of changes involved. Our approach has been based on the concept of 'iterative usability testing', the value of which has recently been emphasized by Shneiderman (1993).